2010
DOI: 10.1007/s00268-010-0636-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pancreaticoduodenectomy on the Course of Hepatic Steatosis

Abstract: The liver attenuation of CT images decreases in patients who receive PD, which implicates that hepatic steatosis can develop after PD; however, the mechanism needs to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 24 publications
3
40
2
Order By: Relevance
“…The prevalence of de novo hepatic steatosis detected on CT scans following pancreaticoduodenectomy showed a wide range like 23.3% (14 of 60 patients) in a Japanese study [7], 66% (33 of 50 patients) in a Taiwanese study [6], 7.8% (15 of 193 patients) in a Korean study [8], and 26.7% (27 of 101 patients) in our study. After considering the differences in homogeneity of patient profiles, diagnostic criteria for fatty change and duration of follow-up period in literature review, it may be reasonable to suggest that at least one fourth of patients develop de novo hepatic steatosis within a few years after pancreaticoduodenectomy.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The prevalence of de novo hepatic steatosis detected on CT scans following pancreaticoduodenectomy showed a wide range like 23.3% (14 of 60 patients) in a Japanese study [7], 66% (33 of 50 patients) in a Taiwanese study [6], 7.8% (15 of 193 patients) in a Korean study [8], and 26.7% (27 of 101 patients) in our study. After considering the differences in homogeneity of patient profiles, diagnostic criteria for fatty change and duration of follow-up period in literature review, it may be reasonable to suggest that at least one fourth of patients develop de novo hepatic steatosis within a few years after pancreaticoduodenectomy.…”
Section: Discussionsupporting
confidence: 49%
“…During outpatient clinic follow-up, we have observed that a considerable proportion of patients who underwent pancreaticoduodenectomy developed de novo hepatic steatosis, which is known as a kind of non-alcoholic fatty liver disease (NAFLD) because most of them did not take alcohol regularly after cancer surgery. It has been previously documented that severe hepatic steatosis sometimes occurs in pancreatectomized patients [4,5,6,7,8,9]. However, the clinical sequences of this type of fatty liver disease have not been fully investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Of 71 studies identified in our broad initial search, we excluded 53 from our review and meta-analysis: those that did not include data from human patients (n=11), 30-40 case reports/series (n=15), 41-55 review articles not providing new information (n=7), 56-62 those not assessing outcomes for pancreatic resection (n=11), 63-73 those failing to provide information about pre-surgical BMI (n=7), [74][75][76][77][78][79][80] and those with equivalent experimental and control group BMI's preventing the extraction of outcomes related to different BMIs (n=2). 81,82 In all, 17 studies were included in the final set (Table 1).…”
Section: Study Populationmentioning
confidence: 99%
“…These values seemed to be lower than those reported in previous studies2, 3, 4, 5, 6, 11, 12 because the development of NAFLD was not evaluated at a fixed time in most of the previous studies. Indeed, we recognized that several patients recovered from NAFLD spontaneously and others deteriorated sequentially, even though they were all taking the same pancreatic enzyme supplements for 1 year (Figure 2).…”
Section: Discussionmentioning
confidence: 55%
“…This steatosis received little interest before the last decade because the patients did not usually have severe hepatic dysfunction clinically even though a few reports documented some cases of hepatic failure after pancreatic resection 8, 9, 10. The prevalence of this steatosis was reported to range from 7.8% to 37%,2, 3, 4, 5, 6, 11, 12 but a few reports are available on the time of occurrence and sequential change in the properties of this complication 13. Etiology of this steatosis may be different from that of conventional nonalcoholic fatty liver disease (NAFLD) related to obesity, dyslipidemia or diabetes mellitus (DM).…”
Section: Introductionmentioning
confidence: 99%